Construction of recombinant adenovirus encoding both TGF-beta 3 and ShRNA targeting type I collagen gene. - Liu, Chengzheng. (2009)
The tissue engineering of Mesenchymal stem cells (MSC) are promising in treatment of cartilage defects and the repairmen of damaged cartilage. But the highly expression of type I collagen in the cells, which will result in fibrocartilage, is still a big problem to be overcome. Basing on RNA interfering (RNAi) and the idea that the TGF-β3 can promote scar-free treatment in previous finding(1), this project was designed to construct an adenoviral vector and thus an adenovirus which can secret TGF-β3 while knocking down the type I collagen expression in target cells. Here the experiments are carried out in human fetal osteoblast (hFOB) cells and human fibroblast (hFB) cells to study the performance of the constructed virus and investigate its possible clinical application.